Fluorinated Bioactive Glass Nanoparticles: Enamel Demineralization Prevention and Antibacterial Effect of Orthodontic Bonding Resin - Hyung-Jin Nam (Materials, 2019)
Orthodontic treatment involving the bonding of fixed appliances to tooth surfaces can cause white spot lesions (WSLs). WSLs increase the likelihood of cavity formation and hence require preservation and prosthetic restoration. Therefore, the prevention of WSLs is of greater importance than treatment. Application of fluoride or the use of fluoride-containing mouthwash can prevent WSLs, but this requires patient cooperation and additional time and cost. Bioactive glass containing 2.5% fluoride was synthesized and mixed with the orthodontic bonding adhesive Transbond XT Low Flow (LV) at ratios of 1, 3, and 5% to prepare orthodontic adhesive samples. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to characterize the samples. The Vickers hardness test, bracket retention test, and adhesive remnant index (ARI) of the samples were analysed to determine their mechanical properties. To determine the biological cytotoxicity, the cell activity of the samples was evaluated using cell viability tests and the antibacterial activity was analysed using Streptococcus mutans. To evaluate the anti-demineralization effect, the sample was bonded to extracted teeth and a pH cycle test was performed. Micro computed tomography data were obtained from the bonded teeth and sample, and the anti-demineralization effect was evaluated using the ImageJ software program. The Vickers hardness of the sample was higher than that of LV and was dependent on the concentration of fluoride-containing bioactive glass (FBAG). The bracket retention test and ARI of the sample showed no significant differences from those of LV. The cell viability test showed no significant changes at 24 and 48 h after application of the sample. The fluoride ion release test indicated an ion release rate of 9.5−17.4 μg/cm2. The antibacterial activity of the experimental group containing FBAG was significantly higher than that of the LV group. The anti-demineralization test showed a concentration-dependent increase. However, the resin containing 5 mass% FBAG (FBAG5) showed a statistically-significant increase compared with LV. The orthodontic adhesive containing FBAG showed antibacterial and anti-demineralization effects, thus indicating possible WSL prevention activity.